The Freinet Pedagogy: nature, society and education - Eloisa Acires Candal Rocha (Universidade Federal de Santa Catarina, 2002)
The impact of the work of the French educator Celestin Freinet contradictory paths traveled in Brazil, perhaps as contradictory as the content and context of construction of his work. Generally absent from curricula of teacher training colleges, even in later periods, Freinet maintained a good part of initiatives to consolidate the project of education "alternative" mainly managed in the decades of 70 and 80 in most urban Brazilians. This experience is revolutionary by nature, is by proposing their own pedagogical strategies that give concrete answers those who seek it counter to traditional educational models based on individuality, and reproduction in the submission of models only.